Postprandial Lipemic Responses to Various Sources of Dietary Fat in Healthy Adults (P08-101-19). (24th October 2019) - Emerson, Sam; Sciarrillo, Christina; Koemel, Nicholas; Bode, Katherine
Abstract: Objectives: Postprandial lipemia (PPL), or a large increase in triglycerides (TG) post-meal, has been identified as an independent risk factor for cardiovascular disease (CVD) and may be a stronger predictor of CVD risk than fasting TG. However, the effects of various sources of dietary fat on PPL are not well understood. Therefore, the objective of this project is to examine the postprandial TG response to commonly consumed sources of dietary fat. Methods: Participants engaged in 4 randomized meal trials separated by at least 1 week. For each meal trial, following a 10-hour overnight fast, an intravenous catheter was inserted into a forearm vein from which a fasting blood draw was taken. Thereafter, participants consumed a standard high-fat meal (HFM; 13 kcal/kg; 61% fat, 32% CHO) with the fat source derived from either butter (B), virgin unrefined coconut oil (CoO), extra virgin olive oil (OO), or canola oil (CaO). Serial blood draws were collected hourly for 6-hours post-meal to quantify postprandial TG responses. Results: Seven healthy participants have completed the protocol (4 M/3F; age 23.8 ± 1.3 years; BMI: 25.5 ± 7.2 kg/m 2 ). Fasting TG was not different ( P  = 0.26) across trials (B: 76.1 ± 41.6 mg/dL; CoO: 69.6 ± 27.1 mg/dL; OO: 75.3 ± 45.7 mg/dL; CaO: 85.1 ± 34.7 mg/dL). Two-way ANOVA revealed a significant time effect ( P  < 0.0001) but no time x meal interaction ( P  = 0.51) or overall meal effect ( P  = 0.10). Meal trials did not differ ( P  = 0.14) with regard to TG total area under the curve (AUC; B: 772.5 ± 449.5 mg/dL × 6 hr; CoO: 605.6 ± 268.2 mg/dL × 6 hr; OO: 726.3 ± 485.3 mg/dL × 6 hr; CaO: 715.1 ± 355.4 mg/dL × 6 hr). However, TG incremental AUC was significantly different ( P  = 0.03) across meal trials (B: 315.6 ± 229.1 mg/dL × 6 hr; CoO: 188.1 ± 151.7 mg/dL × 6 hr; OO: 274.7 ± 246.3 mg/dL × 6 hr; CaO: 204.2 ± 206.7 mg/dL × 6 hr), although no post hoc pairwise comparisons were significantly different (B vs CoO: P  = 0.06; B vs OO: P  = 0.76; B vs CaO: P  = 0.06; CoO vs OO: P  = 0.45; CoO vs CaO: P  = 0.98; OO vs CaO: P  = 0.19). Conclusions: In this continuing experiment, postprandial TG responses to HFMs comprised of different dietary fat sources are largely similar to this point, although a difference in incremental AUC was observed. Upon completion, this study will advance our understanding of the effects of commonly consumed dietary fats on PPL, an indicator of CVD risk. Funding Sources: Institutional internal funding.